(untitled) (Comprehensive Journal of Science, 2025)
Cracks are the most common problem, especially in hot regions (southern Libya). They affect the durability of the building and reduce its lifespan. Cracks are divided into two types: structural cracks and non-structural cracks. Studies have shown that non-structural cracks are the most prevalent. These cracks do not pose any threat to the integrity of the concrete structure if properly treated. They are usually hairline cracks resulting primarily from the natural drying process of concrete or temperature changes. This is normal, especially in areas exposed to high temperatures. Consequently, shrinkage cracks occur. These cracks allow harmful substances such as chlorides, sulphates, and moisture to enter, leading to rusting of the reinforcing steel, thereby weakening the compressive strength, which is one of the most important criteria for determining concrete durability. This reference study aims to investigate the effectiveness of epoxy in treating cracks and improving the mechanical properties of concrete. Epoxy is one of the most common crack repair methods and has numerous advantages, including resistance to moisture and temperature, sealing fixed cracks, and preventing water from seeping through the crack. The study concluded that epoxy is one of the most important materials for repair, as it improves resistance to pressure, tension, and bending.